Feed efficiency improvement and aquaculture waste conversion to economically valuable product - Enang Harris (Jurnal Akuakultur Indonesia)
Fish farmer cannot reduce feed price, however they can reduce feed cost for fish producing. Feed cost is highly determined by feeding rate (FR); whether in maximum FR or restricted FR, and dissolved oxygen level in water. The present paper reviews a detail explanation concerning both factors on feed efficiency. Amongst other water quality parameters, oxygen is the most important factor and therefore must be closely monitored. Moreover, dissolved oxygen cannot be detected only by visual observation. Biofloc technology and PAS (partitioned aquaculture system) can change waste into bacteria and phytoplankton biomass which can be further utilized as fish feed. The major difference between these systems is in the oxygen requirement. This paper also presents some experiment results and preliminary applications in field scale that have been performed in Indonesia.